Rethinking race : beyond the CMIO categorisations - Kathiravelu, Laavanya (Observatory Southeast Asia Ltd, 2022)
The Singaporean media, online civil society space and even parliament was abuzz in August 2011 over an incident where a Singaporean Indian family had limited the cooking of curry in their home after their neighbours, an immigrant Chinese family, had complained to the local mediation centre about the offensive smell of the dish being prepared. The outcome of the mediation, which involved the Indian family agreeing to cook the strong-smelling dish only when their neighbours were not at home, caused furor amongst Singaporeans across races. Claiming curry as a dish enjoyed by all Singaporeans, a “cook a pot of curry” day was declared by a group of citizens and went viral across social media. The incident temporarily overshadowed even the local presidential elections, and caught international attention as part of the backlash against immigrants and foreigners in the city-state.